The Applications of Data-Driven Learning, Corpus-Based Phraseology And Phraseography in the Development of Collocational and Phraseological Competence - Orenha-Ottaiano, Adriane [UNESP] (Taylor & Francis, 2024)
In the sphere of foreign language teaching and learning research, it is important to highlight two major areas of interest in corpus-based investigations: corpus-based phraseology and phraseography. Both research areas have contributed to the development of corpus-based and corpus-driven studies, as well as tools and resources with a view to increase learners’ collocational and phraseological competence, which are key factors for the acquisition of fluency in a foreign language. Guided by a phraseological and phraseographical view, this chapter aims to discuss the relevance and some practical applications of DDL to teach collocations using as a resource tool the Multilingual Collocations Dictionary Platform. This lexicographical resource is described under the theoretical framework of corpus-based phraseology and phraseography, and some corpus-based pedagogical activities targeting English and Portuguese are proposed. Both activities and resources have the aim of promoting foreign language learners’ collocational competence, the latter one under the scope of the funded research project “A phraseographical methodology and model for an online corpus-based Multilingual Collocations Dictionary Platform” (FAPESP Proc nr. 2020/01783-2).